Pengaruh Modal Intelektual Dan Pengungkapan Modal Intelektual Terhadap Profitabilitas Perusahaan Perbankan Yang Terdaftar Di Bei Periode 2019-2022 - Vera Lidia Siahaan; Liza Alvia (Journal on Education, 2024)
This study aims to determine the effect of intellectual capital and intellectual capital disclosure on the profitability of banking companies in the 2019-2022 period. Fluctuations in ROA value are one of the considerations in company profitability. The importance of intellectual capital as one of the assets owned by the company. The thoughts and ideas owned by employees are the basis of intellectual capital. The relevance of financial statements and increasing stakeholder loyalty trust can be done by disclosing intellectual capital. This study uses a quantitative method with 15 banking companies as research samples and sample determination with purposive sampling. The results showed that intellectual capital and intellectual capital disclosure partially or simultaneously showed a negative and insignificant effect on the profitability of banking companies. It can be concluded that the variables of intellectual capital and intellectual capital disclosure do not affect the profitability of banking companies in the 2019-2022 period.